Patient's and healthcare provider's experiences with Opioid Maintenance Treatment (OMT): a qualitative evidence synthesis - Asbjørn Steiro; Christine Hillestad Hestevik; Ashley Elizabeth Muller (BMC, 2024)
Abstract Background Opioid Maintenance Treatment (OMT) is the gold standard for people with opioid dependence. However, drop-out rates are high, and many patients do not reach desired outcomes. Understanding patients' and healthcare providers' experiences with the treatment can provide valuable information to improve the quality of OMT and to increase acceptability and accessibility of services. The aim of this systematic review is to explore and synthesise the experiences of OMT among persons with opioid dependence and health care providers, to inform policy makers and practitioners on how to improve OMT outcomes. Methods We conducted a qualitative evidence synthesis. We systematically searched in electronic databases (CINAHL, Embase, MEDLINE, and nordic databases) and searched for grey literature. As we identified many studies that met our inclusion criteria, we purposively sampled a manageable number of studies to include in this review. Two researchers independently extracted and coded data from the included studies and used the Andersen's healthcare utilization model to organize and develop codes. We assessed the methodological limitations of the studies, and our confidence in the findings using GRADE CERQual. Results We retrieved 56 relevant studies and purposively sampled 24 qualitative studies of patients' and healthcare providers' experiences with OMT. Our analyses resulted in six main themes: (1) External stigma prevents engagement and retention in treatment, (2) Being identified as in OMT contributed to an increased experience of stigma (3) Inadequate knowledge and expertise among healthcare providers affected patients' treatment experiences, (4) Quality of communication between personnel and patients impacts patients' engagement with treatment and treatment outcomes, (5) Patients wanted help with many aspects of their lives not just medication, and (6) Balancing positive expectations of OMT with treatment stigma. We found that stigma was an overarching theme across these themes. Conclusion Our findings suggest that OMT could be more beneficial for patients if treatment programs prioritize efforts to diminish societal and OMT provider stigma and find strategies to better address patient needs. Initiatives should focus on improving treatment knowledge among providers, encouraging the use of client perspectives, considering the context of family members, and establishing a more holistic and flexible treatment environment.